Exploration of the Specific Pathology of HXMM Tablet Against Retinal Injury Based on Drug Attack Model to Network Robustness - Xi, Yujie; Miao, Yan; Zhou, Rui; Wang, Maolin; Zhang, Fangbo; Li, Yu; Zhang, Yi; Yang, Hongjun; Guo, Feifei (Frontiers in Pharmacology, 2022)
Retinal degenerative diseases are related to retina injury because of activation of the complement cascade, oxidative stress-induced cell death mechanisms, dysfunctional mitochondria, chronic neuroinflammation and production of vascular endothelial growth factor (VEGF). Anti-VEGF therapy demonstrates remarkable clinical effect, but also benefits for small part of retinal degenerative disease patients. So, it is necessary for new drug development for patients with severe visual loss. He xue ming mu tablet (HXMM) is a CFDA-approved Traditional Chinese Medicine (TCM)for retinal degenerative diseases, which can alleviate the symptoms of Age - Related Macular Degeneration (AMD), and Diabetic Retinopathy (DR) alone or combining with Anti-VEGF agents. In order to elucidate the mechanisms of HXMM, a quantitative evaluation algorithm for the effect of multi-target drugs on the disturbance of the disease network has been used for exploring specific pathology of HXMM and TCM precision positioning. Compared with anti-VEGF agents, drug disturbance of HXMM to functional subnetwork shows that HXMM reduces the network robustness on oxidative stress subnetwork and inflammatory subnetwork to exhibit the anti-oxidation and anti-inflammation activity. HXMM has well protection of ARPE-19 Cells against retinal injury after H2O2 treatment. HXMM can elevate GSH and reduce LDH level to exhibit anti-oxidant activity, and suppress expression of IL-6 and TNF-α for anti-inflammatory activity, which is different from anti-VEGF agent with strong anti-VEGF activity. The experiment result confirmed the accuracy of the computational prediction. Combination of Bioinformatics prediction based on drug attack to network robustness and experiment validation provide a new strategy for precision application of TCM.